Performance Optimization in Public Health Services: A Human Resource Economics Approach through Workload, Motivation, and Work Environment - Udayani, Putu Kartika; Meitriana, Made Ary; Rahmawati, Putu Indah (International Journal of Economics Development Research (IJEDR), 2025)
This study explores key human resource factors—workload, work motivation, and work environment—and their impact on the performance of health workers, with a focus on organizational efficiency in public health services. The research examines 64 midwives and nurses across 20 public health centers (Puskesmas) in Buleleng Regency, who were assigned additional tasks beyond their formal competencies and educational backgrounds. Data were gathered using an online questionnaire and analyzed using multiple linear regression. The findings reveal that workload negatively and significantly affects performance, while work motivation and work environment have significant positive effects. When considered simultaneously, these three variables contribute positively to performance outcomes. These results highlight the importance of managing human capital effectively to enhance service delivery in public health institutions. The study offers valuable insights for health sector managers and policy makers seeking to improve performance through strategic human resource interventions.